Conference Proceedings on Object-Oriented Programming Systems, Languages, and Applications 1991
DOI: 10.1145/117954.117968
|View full text |Cite
|
Sign up to set email alerts
|

Coherent models for object-oriented analysis

Abstract: Analysis is intended for the formulation and communication of domain descriptions.Consequently, the notations used must be intuitive, expressive and precise. Current object-oriented analysis techniques sat,isfy the first two goals. However, they a.re informal and rely on domain knowledge for establishing semantics and consistency.In this paper, we present a set of formally based coherent models extending current informal techniques. The models have a precise semantics and they constitute a consistent descripti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0
1

Year Published

1996
1996
2005
2005

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(4 citation statements)
references
References 5 publications
0
1
0
1
Order By: Relevance
“…Lano und Haughton [15] geben eine Sammlung von Fallstudien des ersten Ansatzes. Beispiele für den zweiten Ansatz sind in [5,8,11,13] zu finden. Beide Ansätze sind jedoch nicht befriedigend: Die Aufnahme objektorientierter Konzepte in eine formale Methode liefert noch nicht den notwendigen Prozeß zur Entwicklung objektorientierter Software.…”
Section: Notwendigkeit Einer Formalen Objektorientierten Methodeunclassified
“…Lano und Haughton [15] geben eine Sammlung von Fallstudien des ersten Ansatzes. Beispiele für den zweiten Ansatz sind in [5,8,11,13] zu finden. Beide Ansätze sind jedoch nicht befriedigend: Die Aufnahme objektorientierter Konzepte in eine formale Methode liefert noch nicht den notwendigen Prozeß zur Entwicklung objektorientierter Software.…”
Section: Notwendigkeit Einer Formalen Objektorientierten Methodeunclassified
“…In [49][50][51] formalizations are reported that tackle the precursors of UML, namely Rumbaugh's Object Modeling Technique (OMT) diagrams [52] and Jacobson's Object-Oriented Software Engineering [53]. In [49] the authors propose a FOL based formalization for OMT's diagrams and in particular for the object models (OMT's and OOSE's equivalent of UML class diagrams).…”
Section: Related Workmentioning
confidence: 99%
“…In [49][50][51] formalizations are reported that tackle the precursors of UML, namely Rumbaugh's Object Modeling Technique (OMT) diagrams [52] and Jacobson's Object-Oriented Software Engineering [53]. In [49] the authors propose a FOL based formalization for OMT's diagrams and in particular for the object models (OMT's and OOSE's equivalent of UML class diagrams). In [50] the authors formalize an object model in terms of an algebraic specification and its instance diagram 22 in terms of an algebra: the semantics of the object model is the set of algebras which are consistent which the algebraic specification of that model.…”
Section: Related Workmentioning
confidence: 99%
“…The Rigorous Object-Oriented Analysis (ROOA) [15] formalizes object-oriented analysis notations in terms of the LOTOS specification language, with an emphasis on requirements analysis capabilities. Hayes and Coleman [9] have used a VDM-like [11] notation to perform a preliminary formalization of a designspecific subset of the object model of OMT, with an emphasis on incorporating implementation details. Latella, et.…”
Section: Related Workmentioning
confidence: 99%